2015
DOI: 10.1038/srep11062
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Adjuvant Activity of λ-carrageenan by Stimulating Immune Response in Cancer Immunotherapy

Abstract: λ-Carrageenan is a seaweed polysaccharide which has been generally used as proinflammatory agent in the basic research, however, how the immunomodulating activity of λ-carrageenan affects tumor microenvironment remains unknown. In this study, we found that intratumoral injection of λ-carrageenan could inhibit tumor growth in B16-F10 and 4T1 bearing mice and enhance tumor immune response by increasing the number of tumor-infiltrating M1 macrophages, DCs and more activated CD4+CD8+ T lymphocytes in spleen. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 51 publications
(55 reference statements)
1
79
0
1
Order By: Relevance
“…Various polysaccharides, including fucoidan, ascophyllan and λ-carrageenan, have shown immune activation and anti-cancer effects [3, 19, 23, 24]. In this study, we showed that pullulan, a polysaccharide purified from Aureobasidium pullulans , promoted the activation of BMDCs in vitro and of spleen DCs in vivo, and induced anti-cancer immune responses.…”
Section: Discussionmentioning
confidence: 66%
“…Various polysaccharides, including fucoidan, ascophyllan and λ-carrageenan, have shown immune activation and anti-cancer effects [3, 19, 23, 24]. In this study, we showed that pullulan, a polysaccharide purified from Aureobasidium pullulans , promoted the activation of BMDCs in vitro and of spleen DCs in vivo, and induced anti-cancer immune responses.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, carrageenan extracted from red seaweed of the Rhodophyceae family and L. papillosa showed cytotoxicity via inhibition of cell proliferation and induction of apoptosis in human intestinal cancer, breast cancer, and liver cancer cells (31,32). Consistent with the anticancer activity, the administration of λ-carrageenan stimulated the immune system via up-regulation of proinflammatory IL17A and TNF-α, thereby stimulating the activities of tumor infiltrating M1 macrophages, dendritic cells, and T lymphocytes (33). Furthermore, a recent study has confirmed that the extracted sulfated carrageenan (ESC) consists of ι-carrageenan, which infers a direct damage to DNA by modulating nuclear condensation and DNA fragmentation in breast cancer MDA-MB-231 cells.…”
Section: Inhibition Of Cancer Cell Proliferation and Survival Bymentioning
confidence: 76%
“…Accumulating evidence indicates that κ-CGNs, especially their low-MW degradation products, induce inflammation in the colon, resulting in a range of diseases in cell and animal models, including thrombosis [28][29][30][31], peritonitis [26,[32][33][34], paw edema [35,36], pleurisy [37,38], gastroenterocolitis [39,40], arthritis [41,42], and inflammatory bowel disease. However, CGNs also show positive health effects, such as antitumor [43], antimicrobial [44], and antiviral [45,46]. Removal of sulfate esters from sulfated polysaccharides is considered one of the essential steps for microorganisms in the degradation of sulfurized polysaccharides [47].…”
Section: Discussionmentioning
confidence: 99%